Emerging Issues in Nepalese Micro Finance Sector - Dhakal, Nara Hari (Socio-Economic Development Panorama, 2008)
This paper explores emerging issues on Micro Finance (MF) in Nepal and strategies towards developing a sustainable MF sector through a review of the state of the art on developing Nepalese MF sector. The paper has concluded that historically Nepal witness MF as an anti-poverty and development tools and demonstrated a significant paradigm shift on the sector beginning late 1990's and it forward departure as an industry, which benefit thousand of the poor people, poor women, micro-entrepreneurs and peasant farmers and anticipate that the industry should transform further as a lucrative business providing financial services for the poor. In order that all these changes will happen the paper has identified emerging issues such as policy on macro-economy and financial system stability, regulation and supervision of MF sector, institutional capacity building, expanding the frontier of MF services in remote areas, introduction of Information and Communication Technology (ICT), encroachment or unfair competition and financial viability and uncovered the clear need to address these issues properly and in time. Socio-Economic Development Panorama, Vol. 1, No. 2(2007) pp. 35-46